Managing disaster risks to cultural heritage from risk preparedness to recovery for immovable heritage - Romão, Xavier; Rouhani, Bijan (Routledge, Taylor & Francis Group, 2024)
"Managing Disaster Risks to Cultural Heritage presents case studies from different regions in the world and establishes a framework for understanding, identifying, and analysing disaster risks to immovable cultural heritage. Including contributions from academics and practitioners from around the globe, the book presents a comprehensive view of the scholarship relating to cultural heritage, disaster risk preparedness and post-disaster recovery. Particular attention is given to the complex and dynamic nature of disaster risks and how they evolve during different phases of a catastrophic event, especially as hazards can create secondary effects that have greater impacts on cultural heritage, infrastructure, and economy. Arguing that risk preparedness and mitigation have historically been secondary to reactive emergency and first aid response, the book demonstrates that preparedness plans based on sound risk assessments can prevent hazards from becoming disasters. Emphasising that the protection of cultural heritage through preparedness and mitigation actions and risk adaptation measures, especially for climate change, can contribute to the resilience of societies, the book highlights the vital role of communities in such activities. Managing Disaster Risks to Cultural Heritage will be useful to students, professionals, and scholars studying and working with cultural heritage protection. It will be of particular interest to those working in the Cultural Heritage, Archaeology, Conservation and Preservation, Sustainable Development and Disaster Studies fields"--